A vida como desígnio da arte : a relação entre arte e pessimismo nas primeiras obras de Friedrich Nietzsche - Camilo Lelis Jota Pereira (2021)
This thesis addresses the problem of pessimism as a basis for understanding the initial works of philosopher Friedrich Nietzsche, particularly The birth of tragedy. The problem of pessimism is consolidated as a philosophical debate in the 19th century through the prominence of Arthur Schopenhauer’s philosophy, which defends the thesis of the lack of justifications for human life. In this context, we will focus on the relationship between art and pessimism in Nietzsche’s early work, analyzing a particular understanding that the philosopher makes of the thesis defended by Schopenhauer, leading to the conception that existence is only justified as an aesthetic phenomenon. We will show that this point articulates all Nietzsche’s theory on the musical aesthetics of Greek tragedy. To this end, we argue that: 1) Nietzsche is committed to the Hellenistic and classicist political debate on the guidelines that should guide German culture; 2) Schopenhauer’s influence on The birth of tragedy owes much to the problem of pessimism; 3) Nietzsche creates a particular definition for pessimism under the motto of the Dionysian. This argument is divided into 4 chapters, reconstructing the philosopher’s onslaught on opposition pessimism-optimism. Finally, we maintain that the problem of justification of existence, which underlies Pessimismus-Frage, is handled by Nietzsche by showing that, when put in good hands, pessimism is not a problem, but rather the promotion of a specific form of freedom manifested in the Greek tragedy